The final case - Guterson, David (Alfred A. Knopf, 2022)
"A provocative new novel from the best-selling author of Snow Falling on Cedars--a moving father-son story that is also a taut courtroom drama and a bold examination of privilege, power, and how to live a meaningful life. In a small rural town outside Seattle, Joanna, an Ethiopian girl adopted by a white fundamentalist Christian family, is found dead of hypothermia in her own backyard--setting in motion a gripping journey into the complexities of human emotion. How does it feel to be a child taken into a family that doesn't share her background, her religion, or the color of her skin? What does it mean to be a mother on trial for murder? And why would a lawyer choose to defend such a woman? Royal is a criminal attorney in his eighties, and this is his final case. His son, our narrator, drives Royal every day from his office to the town where the tragedy took place, and observes the trial as it unfolds. The consequences will reach beyond what he could have anticipated. Bracing, astute, and intensely imagined, The Final Case is a tightrope walk of a novel, a deeply affecting work of fiction that dares to confront life's most irreconcilable moral quandaries. It will make an indelible impression on every reader"--